2021
DOI: 10.1111/febs.16303
|View full text |Cite
|
Sign up to set email alerts
|

Distinct binding kinetics of E‐, P‐ and L‐selectins to CD44

Abstract: Molecular‐level selectin‐cluster of differentiation 44 (CD44) interactions are far from clear because of the complexity and diversity of CD44 glycosylation and isoforms expressed on various types of cells. By combining experimental measurements and simulation predictions, the binding kinetics of three selectin members to the recombinant CD44 were quantified and the corresponding microstructural mechanisms were explored, respectively. Experimental results showed that the E‐selectin–CD44 interactions mainly medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…2). In addition, the effective cell accumulation that only occurred below a shear stress of 1.0 dyne·cm −2 indicated that CD44–HA association was not as fast as that of selectin‐ligand interactions [37,38]. On the other hand, our results revealed that the disruption of CD44 clustering regulated the CD44–HA interaction and corresponding cell adhesion (Fig.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…2). In addition, the effective cell accumulation that only occurred below a shear stress of 1.0 dyne·cm −2 indicated that CD44–HA association was not as fast as that of selectin‐ligand interactions [37,38]. On the other hand, our results revealed that the disruption of CD44 clustering regulated the CD44–HA interaction and corresponding cell adhesion (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…A Bioscope MultiMode8 AFM (Bruker, Billericia, MA, USA) was used to measure the binding strength of CD44–HHA/LHA interactions [37]. Commercial MLCT cantilevers (Veeco; Bruker) were used with a nominal spring constant k c of 10 pN·nm −1 (cantilever C ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another approach targeting NP delivery to tumor cells used an acrylamide-based doxorubicin nanogel (DOX-NG) fabricated by the single emulsion method [ 217 ]. For targeting, the DOX-NGs were coated with platelet membrane since platelets express p -selectin [ 258 ], a molecule that binds to CD44, a receptor often up-regulated on cancer cells [ 259 ]. Finally, the coated DOX-NPs were functionalized with TRAIL using cysteine thiol-conjugation.…”
Section: Trail Formulations To Mimic Membrane-bound Trailmentioning
confidence: 99%